The effect of prey quality and ice conditions on the nutritional status of Baltic gray seals of different age groups - Kauhala, Kaariina; Bäcklin, Britt-Marie; Raitaniemi, Jari; Harding, Karin C. (Springer, 2017)
We analyzed a long-term data set of the body condition of Baltic gray seals (Halichoerus grypus) over time and investigated how average subcutaneous blubber thickness of different age groups of seals corresponds to environmental factors. Blubber thickness of pups declined until 2010. The decreasing weight of 5–6-year-old herring (Clupea harengus), the main prey fish for Baltic gray seals, explained well the decline. In the Gulf of Finland, the blubber thickness of pups declined also in recent years (2011–2015) with declining number of days with permanent ice cover. In other regions, the blubber thickness of pups increased during recent years with increasing weight of herring. The blubber thickness of subadults in Baltic Proper and that of hunted adult females in the Bothnian Bay also increased during recent years, and the weight of age 6+ or 7-year-old herring best explained the increase. The blubber thickness of all age groups of seals was thinnest in the Bothnian Bay where also herring weight was lowest. There was a negative correlation between blubber thickness of seals and herring catch size (an index of herring abundance) suggesting that herring quality, not the quantity, is important for the nutritional status of Baltic gray seals. Nutritional status of gray seals may thus reveal changes in the marine food web which affect herring quality. Marine food web, in turn, may be affected, e.g., by climate change. The warming climate also has an impact on ice cover and thus body condition of seal pups.
Keywords: Baltic food web; blubber thickness; food chains; thickness; climate change; Halichoerus grypus; herrings